HUBUNGAN ANTARA MINAT MEMBACA DENGAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELA IV SD NEGERI 92 SINGKAWANG - Carollin Febrianty; ABD. Basith; Wahyuni Oktavia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine 1) how is the interest in reading, 2) how is the skill of writing narrative essays, and 3) how big is the relationship between interest in reading and the skill of writing narrative essays of fourth grade students at SDN 92 Singkawang. The type of research used is quantitative with a correlational research design. The population in this study were fourth grade students of SDN 92 Singkawang. In this study there were 28 students used as research samples. Data collection techniques used non-test techniques and test techniques. Data were analyzed using a correlation test with a level of 0.05 and looked for variable contributions. The results of the study showed that 1) interest in reading, 2) skills in writing narrative essays, and 3) the relationship between interest in reading and students' skills in writing narrative essays there is a significant relationship (correlation) between interest in reading and students' skills in writing narrative essays. With a correlation coefficient of 0.415 which means it has a moderate relationship based on the correlation level. Interest in reading has a contribution of 17%. The implications of this study indicate that there needs to be an effort to increase students' interest in reading so that it can have a positive impact on narrative essay writing skills.